Técnica de esgrafiado en la disminución del estrés en una institución del nivel primario de Huancavelica - Arroyo Ñahui, Lisbeth Malena (2024)
The research aimed to determine the degree of influence of the sgraffito technique in reducing stress in the students of the 2nd Grade “C” of the Educational Institution No. 36002 Las Azules in Huancavelica during the 2022 academic period. The research had a quantitative approach.  applied type, explanatory level, with a pre-experimental design. The population consisted of 91 students, with a non-probabilistic sample of 24 children. The scientific method and logical methods were applied, and the techniques and instruments used included systematic observation (sgraffito observation sheet) and a survey (stress questionnaire). The results indicated that before applying the sgraffito technique, 58.3% of students exhibited moderate stress and 41.7% showed high stress across both dimensions. However, after applying the technique, stress levels shifted to 70.8% low and 29.2% moderate. Statistical analysis using the non-parametric Wilcoxon test revealed a significance level of sig. = 0.000, which is highly significant, because it is lower than the assumed significance level α=0.05. The study concludes that the sgraffito technique effectively reduces emotional and physical stress of the students of the 2nd Grade “C” of the Educational Institution No. 36002 Las Azules in Huancavelica.